Legal Review of States Financial Assistance for Political Parties According Democracy Perspective - Lewerissa, Samuel Suiq; Syahuri, Taufiqqrohman Syahuri; Triadi, Irwan (PT. Riset Press International, 2025)
The financial sources of political parties as stated in Article 34 paragraph (1) of Law Number 2 of 2011 concerning Political Parties are, membership fees, legally valid donations and financial assistance from the state. Financial assistance from the state through the State Budget/Regional Budget. Assistance from the state based on Article 34 paragraph (3) is given only to political parties that get seats in the legislative institution. This study aims to analyze financial assistance from the state to political parties in accordance with the principles of ideal democracy. With a normative legal approach, this study found that although regulations have regulated financial assistance to political parties, this assistance is only given to political parties that get seats in the legislative institution. Therefore, in order to realize an ideal democracy, financial assistance from the state should also be given to political parties that do not get seats in the legislative institution but participate in the general election contest, because all political parties have the same rights, obligations and functions without exception, as mandated in the laws and regulations. With this step, it is hoped that a democratic system will be realized for each political party.